Salat Gaib untuk Korban Bencana Alam dalam Perspektif Hukum Islam - Saifullah bin Anshor; Rachmat Bin Badani Tempo; Asri (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed at elaborating and identifying the law and the virtues of funeral prayer, the definition of absentee funeral prayer, the propositions of the inquiry of absentee funeral prayer, scholars’ opinions on the law of absentee funeral prayer, the ruling of absentee funeral prayer, time and distance limit in absentee funeral prayer, and the law of absentee funeral prayer on the victims of natural disasters. This study employed qualitative-descriptive method with normative approach techniques and library research. The result of the study shows that: (1) The law of absentee funeral prayer is permissible on the corpse that is not yet prayed on; (2) The ruling of absentee funeral prayer is the same as the ruling of funeral prayer; (3) There is no time limit for performing absentee funeral prayer on condition that the person dies at the time person who wants to perform prayer has been able to perform prayer; (4) The distance limit of absentee funeral prayer is the distance in which it is difficult to be visited by people who want to perform prayer; (5) The natural disaster victim, if his or her body is not found and is not yet prayed on, then he/she can be prayed on in absentia.